c for Collaborative Model for Integrated Waste Management in Gresik Regency, East Jawa - Diana, Diana Hertati (Advances in Social Sciences Research Journal, 2021)
The issue of solid waste is increasingly urgent to be handled by the Gresik district government. Population growth and socio-economic activities in this area have a positive correlation with the increase in the amount and type of waste. This condition will certainly threaten the regional ecosystem, so collaboration between the government, the community and the private sector is needed in integrated waste management. The research objectives are to identify the existing condition of integrated waste management in Gresik Regency, to map the driving and inhibiting factors in integrated waste management and to formulate a model format for an integrated waste management paradigm change. The research method uses a qualitative descriptive approach to obtain a complete description of the collaboration model in integrated waste management. Sources of data obtained from secondary data, literature studies, interviews and observations. Informants consist of the Head of the Department of Cleanliness and the Environment and his staff, the public and the private sector. Methods of data collection is done by using interviews, focused group and discussion. Data analysis was carried out using qualitative analysis from Miles and Huberman consisting of four components, namely: data collection (data collection), data condensation (data condensation), data presentation (data display) and conclusion drawing or verification (conclusion and verifying drawing). The results of the study indicate that waste management in Gresik Regency which is carried out in an integrated manner with the collaborative involvement of stakeholders has not been able to be carried out optimally and completely until it reaches the Final Disposal Site. The potential of resources owned by the Gresik Regency Government structurally has not been able to optimally solve problems in waste management. There are encouraging and inhibiting factors originating from the systemic conditions of the Gresik Regency Government which do not run proportionally in overcoming the problem of waste management. The existence of an alternative model of changing the paradigm of integrated waste management is possible to overcome the problems of waste management in Gresik Regency.